TAX COMPLIANCE AND MORAL ETHICS DIFFERENCES ACROSS BABY BOOMER II, GENERATION X, MILLENNIALS AND GENERATION Z - Garing, Dealova Ninditia Evelin; Evangeline, Angela; Nathanael, Kensi Isa; Magdalena, Renna (Jurnal Ilmiah Manajemen, Ekonomi, & Akuntansi (MEA), 2024)
This study aims to analyze the differences in tax compliance and tax morality ethics among generations in Indonesia, involving four generational groups: Baby Boomer II, Generation X, Millennials, and Generation Z. The methodology used is quantitative with a survey approach, utilizing questionnaires distributed in Jakarta, Surabaya, and Bekasi. The main findings indicate significant differences in tax compliance and tax morality ethics across generations, where Generation X shows the highest tax compliance and Generation Z has the lowest tax morality ethics. This research provides insights for the government to design more effective tax policies tailored to generational characteristics.